Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To determine which function has two [tex]\(x\)[/tex]-intercepts, one at [tex]\((0,0)\)[/tex] and one at [tex]\((4,0)\)[/tex], we need to examine the given functions to find their intercepts.
### 1) [tex]\( f(x) = x(x - 4) \)[/tex]
First, set [tex]\( f(x) = 0 \)[/tex] to find the [tex]\(x\)[/tex]-intercepts:
[tex]\[ x(x - 4) = 0 \][/tex]
Solving for [tex]\(x\)[/tex], we get:
[tex]\[ x = 0 \quad \text{or} \quad x - 4 = 0 \][/tex]
[tex]\[ x = 0 \quad \text{or} \quad x = 4 \][/tex]
These intercepts are [tex]\((0, 0)\)[/tex] and [tex]\((4, 0)\)[/tex].
### 2) [tex]\( f(x) = x(x + 4) \)[/tex]
Set [tex]\( f(x) = 0 \)[/tex]:
[tex]\[ x(x + 4) = 0 \][/tex]
Solving for [tex]\(x\)[/tex], we get:
[tex]\[ x = 0 \quad \text{or} \quad x + 4 = 0 \][/tex]
[tex]\[ x = 0 \quad \text{or} \quad x = -4 \][/tex]
These intercepts are [tex]\((0, 0)\)[/tex] and [tex]\((-4, 0)\)[/tex].
### 3) [tex]\( f(x) = (x - 4)(x - 4) \)[/tex]
Set [tex]\( f(x) = 0 \)[/tex]:
[tex]\[ (x - 4)(x - 4) = 0 \][/tex]
Solving for [tex]\(x\)[/tex], we get:
[tex]\[ x - 4 = 0 \][/tex]
[tex]\[ x = 4 \][/tex]
This intercept is [tex]\((4, 0)\)[/tex], but it is a repeated root, so there's only one unique intercept at [tex]\((4, 0)\)[/tex].
### 4) [tex]\( f(x) = (x + 4)(x + 4) \)[/tex]
Set [tex]\( f(x) = 0 \)[/tex]:
[tex]\[ (x + 4)(x + 4) = 0 \][/tex]
Solving for [tex]\(x\)[/tex], we get:
[tex]\[ x + 4 = 0 \][/tex]
[tex]\[ x = -4 \][/tex]
This intercept is [tex]\((-4, 0)\)[/tex], but it is a repeated root, so there's only one unique intercept at [tex]\((-4, 0)\)[/tex].
### Conclusion
From the analysis above, the function [tex]\( f(x) = x(x - 4) \)[/tex] has [tex]\( x \)[/tex]-intercepts at [tex]\((0,0)\)[/tex] and [tex]\((4,0)\)[/tex].
Thus, the correct function is:
[tex]\[ \boxed{f(x) = x(x - 4)} \][/tex]
### 1) [tex]\( f(x) = x(x - 4) \)[/tex]
First, set [tex]\( f(x) = 0 \)[/tex] to find the [tex]\(x\)[/tex]-intercepts:
[tex]\[ x(x - 4) = 0 \][/tex]
Solving for [tex]\(x\)[/tex], we get:
[tex]\[ x = 0 \quad \text{or} \quad x - 4 = 0 \][/tex]
[tex]\[ x = 0 \quad \text{or} \quad x = 4 \][/tex]
These intercepts are [tex]\((0, 0)\)[/tex] and [tex]\((4, 0)\)[/tex].
### 2) [tex]\( f(x) = x(x + 4) \)[/tex]
Set [tex]\( f(x) = 0 \)[/tex]:
[tex]\[ x(x + 4) = 0 \][/tex]
Solving for [tex]\(x\)[/tex], we get:
[tex]\[ x = 0 \quad \text{or} \quad x + 4 = 0 \][/tex]
[tex]\[ x = 0 \quad \text{or} \quad x = -4 \][/tex]
These intercepts are [tex]\((0, 0)\)[/tex] and [tex]\((-4, 0)\)[/tex].
### 3) [tex]\( f(x) = (x - 4)(x - 4) \)[/tex]
Set [tex]\( f(x) = 0 \)[/tex]:
[tex]\[ (x - 4)(x - 4) = 0 \][/tex]
Solving for [tex]\(x\)[/tex], we get:
[tex]\[ x - 4 = 0 \][/tex]
[tex]\[ x = 4 \][/tex]
This intercept is [tex]\((4, 0)\)[/tex], but it is a repeated root, so there's only one unique intercept at [tex]\((4, 0)\)[/tex].
### 4) [tex]\( f(x) = (x + 4)(x + 4) \)[/tex]
Set [tex]\( f(x) = 0 \)[/tex]:
[tex]\[ (x + 4)(x + 4) = 0 \][/tex]
Solving for [tex]\(x\)[/tex], we get:
[tex]\[ x + 4 = 0 \][/tex]
[tex]\[ x = -4 \][/tex]
This intercept is [tex]\((-4, 0)\)[/tex], but it is a repeated root, so there's only one unique intercept at [tex]\((-4, 0)\)[/tex].
### Conclusion
From the analysis above, the function [tex]\( f(x) = x(x - 4) \)[/tex] has [tex]\( x \)[/tex]-intercepts at [tex]\((0,0)\)[/tex] and [tex]\((4,0)\)[/tex].
Thus, the correct function is:
[tex]\[ \boxed{f(x) = x(x - 4)} \][/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.